<math><mstyle displaystyle="true"><mtable class="shapeTable" columnlines="solid" rowlines="solid"><mtr><mtd><mi>Side</mi></mtd><mtd><mi>Angle</mi></mtd></mtr><mtr><mtd><mtable><mtr><mtd><mrow><mi>b</mi><mo>=</mo></mrow></mtd><mtd><mn>4</mn></mtd></mtr><mtr><mtd><mrow><mi>c</mi><mo>=</mo></mrow></mtd><mtd><mn>5</mn></mtd></mtr><mtr><mtd><mrow><mi>a</mi><mo>=</mo></mrow></mtd><mtd><mn>3</mn></mtd></mtr></mtable></mtd><mtd><mtable><mtr><mtd><mrow><mi>A</mi><mo>=</mo></mrow></mtd><mtd></mtd></mtr><mtr><mtd><mrow><mi>B</mi><mo>=</mo></mrow></mtd><mtd></mtd></mtr><mtr><mtd><mrow><mi>C</mi><mo>=</mo></mrow></mtd><mtd></mtd></mtr></mtable></mtd></mtr></mtable></mstyle></math>

Find the opposite side of the unit circle triangle. Since the adjacent side and hypotenuse are known, use the Pythagorean theorem to find the remaining side.

Replace the known values in the equation.

Raise <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> to the power of <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Opposite <math><mstyle displaystyle="true"><mo>=</mo><msqrt><mn>25</mn><mo>-</mo><msup><mrow><mo>(</mo><mn>4</mn><mo>)</mo></mrow><mrow><mn>2</mn></mrow></msup></msqrt></mstyle></math>

Raise <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> to the power of <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Opposite <math><mstyle displaystyle="true"><mo>=</mo><msqrt><mn>25</mn><mo>-</mo><mn>1</mn><mo>⋅</mo><mn>16</mn></msqrt></mstyle></math>

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>16</mn></mstyle></math> .

Opposite <math><mstyle displaystyle="true"><mo>=</mo><msqrt><mn>25</mn><mo>-</mo><mn>16</mn></msqrt></mstyle></math>

Subtract <math><mstyle displaystyle="true"><mn>16</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>25</mn></mstyle></math> .

Opposite <math><mstyle displaystyle="true"><mo>=</mo><msqrt><mn>9</mn></msqrt></mstyle></math>

Rewrite <math><mstyle displaystyle="true"><mn>9</mn></mstyle></math> as <math><mstyle displaystyle="true"><msup><mrow><mn>3</mn></mrow><mrow><mn>2</mn></mrow></msup></mstyle></math> .

Opposite <math><mstyle displaystyle="true"><mo>=</mo><msqrt><msup><mrow><mn>3</mn></mrow><mrow><mn>2</mn></mrow></msup></msqrt></mstyle></math>

Pull terms out from under the radical, assuming positive real numbers.

Opposite <math><mstyle displaystyle="true"><mo>=</mo><mn>3</mn></mstyle></math>

Opposite <math><mstyle displaystyle="true"><mo>=</mo><mn>3</mn></mstyle></math>

Use the definition of cosine to find the value of <math><mstyle displaystyle="true"><mi>cos</mi><mrow><mo>(</mo><mi>A</mi><mo>)</mo></mrow></mstyle></math> .

Substitute in the known values.

Use the definition of sine to find the value of <math><mstyle displaystyle="true"><mi>sin</mi><mrow><mo>(</mo><mi>A</mi><mo>)</mo></mrow></mstyle></math> .

Substitute in the known values.

Use the definition of tangent to find the value of <math><mstyle displaystyle="true"><mi>tan</mi><mrow><mo>(</mo><mi>A</mi><mo>)</mo></mrow></mstyle></math> .

Substitute in the known values.

Use the definition of cotangent to find the value of <math><mstyle displaystyle="true"><mi>cot</mi><mrow><mo>(</mo><mi>A</mi><mo>)</mo></mrow></mstyle></math> .

Substitute in the known values.

Use the definition of secant to find the value of <math><mstyle displaystyle="true"><mi>sec</mi><mrow><mo>(</mo><mi>A</mi><mo>)</mo></mrow></mstyle></math> .

Substitute in the known values.

Use the definition of cosecant to find the value of <math><mstyle displaystyle="true"><mi>csc</mi><mrow><mo>(</mo><mi>A</mi><mo>)</mo></mrow></mstyle></math> .

Substitute in the known values.

This is the solution to each trig value.

Do you know how to Find the Trig Values Using Angle A tri{4}{}{5}{}{3}{}? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.